Devastating Effect of Covid-19 Pandemic on Polish Hospitality Sector - Mariusz CEMBRUCH-NOWAKOWSKI (Communications of International Proceedings, 2021)
The steadily growing hospitality sector in Poland was severely affected by the Covid-19 pandemic.  The paper presents the preliminary studies demonstrating the changes induced by pandemic in some important parameters of that sector. Although the pandemic has not stopped and the situation is still unclear it is important to identify the problems and monitor the changes in view of necessity to find the instrument and methods to provide the  necessary help to that branch of economy.